A Needs Analysis for an English for Occupational Purposes (EOP) Accounting Course - Blanco Navarro, Randal Esteban (2023)
The teaching of English for occupational purposes relies on the insights that a detailed needs analysis on the student-client population provides. This paper reports the findings of a Needs Analysis (NA) conducted on the occupational purposes of accountants in Golfito, a county in the southern region of Costa Rica. It also describes the participant population and narrates the historical development of this academic project. Some NA theoretical principles have been considered during the design and implementation of four data collection instruments: questionnaires, interviews, a desk analysis, and a focus group. The main objective has been to identify the communicative target situations that accountants and accounting employees face in their workplaces in this rural area. Therefore, adult learners with diverse English language proficiency levels enriched this NA by answering three questionnaires, providing two interviews, and contributing to a focus group. The main findings include the participants’ needs to explain financial statements in English, boost their L2 accounting vocabulary, and describe Costa Rican tax filing procedures to their stakeholders, especially those who are foreign business owners. This paper yields promising insights on their occupational needs that would support the language curriculum design process of a twelve-week EOP accounting course.